An Application of Multiple Regression in Exchange Rate Arrangements - Ndiritu, Gachiri Charles (University of the Western Cape, 2013)
Magister Scientiae - MSc === This project "An application of multiple regression in exchange rate arrangement" focused on the processes followed by different countries when choosing an exchange rate regime for currency stabilization. It analyses the consequences faced by emerging markets as a result of changes in volatility of developed countries’ currencies (American Dollar, Japanese Yen, EURO, British Pound and the Canadian Dollar). === South Africa